2007
DOI: 10.1002/mrd.20725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre‐treating in vitro‐matured bovine oocytes with the cytoskeleton stabilizing agent taxol prior to vitrification

Abstract: The purpose of this study was to determine the efficacy of pre-treating mature bovine oocytes with Taxol before vitrification by the open pulled Straw method (OPS). We evaluated the effects of pre-treating the oocytes with 1 microM Taxol on chromosome organization, spindle morphology, cortical granule distribution and the ability of fertilized oocytes to develop to the blastocyst stage. After calf or cow oocyte vitrification without Taxol, significantly higher proportions of spindle abnormalities in the form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 50 publications
3
45
0
3
Order By: Relevance
“…The achievements of vitrification with our newly developed carrier are comparable to results achieved by following research teams using similar vitrification protocol and open carriers (Luna et al 2001;Diez et al 2002;Vieira et al 2002;Modina et al 2004;Albarracín et al 2005;Morató et al 2008aMorató et al , 2008bMorató et al , 2008cand Hou et al 2009). Hence, we can declare this new carrier a safe variant for bovine oocyte vitrification, which is inexpensive to manufacture from affordable components.…”
Section: Discussionsupporting
confidence: 77%
“…The achievements of vitrification with our newly developed carrier are comparable to results achieved by following research teams using similar vitrification protocol and open carriers (Luna et al 2001;Diez et al 2002;Vieira et al 2002;Modina et al 2004;Albarracín et al 2005;Morató et al 2008aMorató et al , 2008bMorató et al , 2008cand Hou et al 2009). Hence, we can declare this new carrier a safe variant for bovine oocyte vitrification, which is inexpensive to manufacture from affordable components.…”
Section: Discussionsupporting
confidence: 77%
“…Taxol interacts with microtubules and increases the rate of polymerization by reducing the critical concentration of tubulin needed for polymerization. The addition of Taxol to the vitrification solution improves the post-warming development of immature human (Fuchinoue et al 2004) and mature porcine (Shi et al 2006) and bovine (Morato et al 2008) oocytes.…”
Section: Others Cryoprotectants and New Strategies To Improve Cryotolmentioning
confidence: 98%
“…Many problems were found to be associated with chilling and freezing of immature, in vitro matured or ovulated oocytes, including abnormal spindle associated with disorganized microtubules and chromosomes (Rojas et al 2004;Succu et al 2007), altered distribution of cortical granules and increased polispermy or on the contrary, zona pellucida hardening by premature cortical granule exocitosis impairing fertilization (Mavrides and Morrol 2005;Morato et al 2008).…”
Section: Oocyte and Embryo Cryoinjuriesmentioning
confidence: 99%
“…Paclitaxel is known to stabilize the microtubules that constitute the spindle [15]. It has been reported that the normality of the spindles of MII-stage oocytes immediately after freezing can be improved by paclitaxel treatment in both pigs [16] and cattle [17]. Furthermore, the developmental potency of cryopreserved MII-stage oocytes has been shown to be improved by paclitaxel treatment in mice [18], cattle [19], sheep [20] and pigs [16].…”
mentioning
confidence: 99%